2008
DOI: 10.1097/01.naj.0000337736.76730.66
|View full text |Cite
|
Sign up to set email alerts
|

Lead Hazards for Pregnant Women and Children: Part 1

Abstract: Poor, urban, and immigrant populations are at far greater risk for lead exposure than are other groups in the United States. Children with even slightly elevated blood lead levels are at increased risk for significant neurobehavioral problems that can extend through adolescence. Research has shown that elevated blood lead levels in pregnant women, even those well below 10 micrograms per deciliter-the Centers for Disease Control and Prevention's "level of concern"-can cause miscarriage, premature birth, low bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Children, especially younger children, are at greatest risk for elevated BLLs. Some studies have demonstrated that children appear to have approximately four to five times higher lead absorption than adults [ 10 ], and the detoxification capability of lead in adults was three times higher than in children [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children, especially younger children, are at greatest risk for elevated BLLs. Some studies have demonstrated that children appear to have approximately four to five times higher lead absorption than adults [ 10 ], and the detoxification capability of lead in adults was three times higher than in children [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lead is a naturally occurring element in the environment but has no known biological role within the human body. Uncommon sources of inadvertent human lead exposure include imported foods, Ayurvedic medications, household items, and toys [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Lead oxide glaze, known as Bgreta,^is commonly used in the manufacture of ceramic cooking vessels in Hispanic communities; use of imported lead-glazed ceramic dishes has been recognized as a risk factor for lead toxicity in Hispanic populations [6]. Over time, lead may leach out of pottery glazes; acidity and heat may increase the risk of this occurrence [1,6]. In our case, the acidity of the lemon and the heat of the water used from the patient's instant hot water tap likely increased the rate of glaze breakdown and leaching from the ceramic mug, leading to lead exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pregnant woman's elevated blood lead level can lead to miscarriage, prematurity, low birth weight, and problems with development during childhood 11 . Lead induces disturbances in the development of different types of WBCs during postnatal development and lead to an abrupt neutrophilic degeneration, immature cells, abnormal neutrophils, reactive and plasmacytoid lymphocytes 12 .…”
mentioning
confidence: 99%